ANALGESIC EFFECT AYURVEDIC MEDICINE MADHUKA MANJISHTA RAKTACHANDANDI LEPAM IN ACUTE KNEE INJURY: A CASE STUDY - Praveen P.P; Om Prakasah Dave; Dr. Praneetha Kesavan (The Bioscan, 2025)
This case study explores the analgesic and anti-inflammatory effects of hydrogel made from the alcoholic extract (90:10) of Ayurvedic medicine Madhuka manjishta raktachandanadi lepam on acute knee injuries. It focuses on a 22-year-old male footballer and shop assistant with severe pain and restricted mobility following a sports-related injury. The study examines the efficacy of the topical application of Ayurvedic medicine Madhuka manjishta raktachandana lepam in alleviating symptoms and supporting recovery. It aims to provide broader insights into the potential clinical applications of this herbal intervention.